2015
DOI: 10.1002/jbm.b.33368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated oxidation on thein vitrowear and mechanical properties of irradiated and melted highly crosslinked UHMWPE

Abstract: Radiation crosslinked ultrahigh molecular weight polyethylene (UHMWPE) have reduced the wear rate of the bearing surface in total joint arthroplasty and the incidence of peri-prosthetic bone loss due to wear particles. The oxidation potential afforded to the material by the trapped residual free radicals after irradiation was addressed in first generation crosslinked UHMWPEs by using thermal treatments such as annealing or melting after irradiation. Postirradiation melted crosslinked UHMWPE did not contain det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 52 publications
0
26
1
Order By: Relevance
“…Historically, an oxidation level of one was associated with a physically meaningful reduction in the mechanical properties of conventional, gamma sterilized UHMWPE . It also has to be noted that the mechanical strength of irradiated and melted UHMWPEs is substantially lower than unoxidized conventional UHMWPE; therefore, the oxidation rates and thresholds for clinically relevant mechanical deterioration for these highly cross‐linked UHMWPEs may be different than those for conventional UHMWPE . An analysis of the oxidation‐depth profiles, oxidation products, and the effect of oxidation on the crosslink density of retrievals as well as the development and refinement of clinically relevant accelerated aging methods is necessary and useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, an oxidation level of one was associated with a physically meaningful reduction in the mechanical properties of conventional, gamma sterilized UHMWPE . It also has to be noted that the mechanical strength of irradiated and melted UHMWPEs is substantially lower than unoxidized conventional UHMWPE; therefore, the oxidation rates and thresholds for clinically relevant mechanical deterioration for these highly cross‐linked UHMWPEs may be different than those for conventional UHMWPE . An analysis of the oxidation‐depth profiles, oxidation products, and the effect of oxidation on the crosslink density of retrievals as well as the development and refinement of clinically relevant accelerated aging methods is necessary and useful.…”
Section: Discussionmentioning
confidence: 99%
“…of O 2 at 70°C for 14 days) . Although this standardized test is able to induce oxidation in UHMWPEs with free radicals and in UHMWPEs without free radicals in non‐standardized long durations, it is unable to simulate accurately the oxidation rate and oxidation‐depth profiles observed in vivo. It is possible that oxidation of UHMWPE is affected by lipid absorption in vivo, a factor which was previously not considered in the development of in vitro accelerated aging methods.…”
mentioning
confidence: 99%
“…After irradiation and annealing, numerous crosslinked networks were formed in X‐UHMWPE. These crosslinked networks had smaller COFs and wear rates compared with the pristine UHMWPE and hardened the composite . The COFs and wear rates of the crosslinked parts apparently decreased with absorbed dose, especially when the dose was not large .…”
Section: Resultsmentioning
confidence: 96%
“…This process increases the molecular weight and induces the formation of crosslinking networks. These characteristics sufficiently improve the mechanical properties of UHMWPE such as creep resistance, hardness, wear resistance, and yield strength . Some studies have reported that the wear rate decreased by 90% through radiation crosslinking at a dose of 100 kGy .…”
Section: Introdutionmentioning
confidence: 96%
See 1 more Smart Citation